A calibration procedure for reconfigurable Gough-Stewart manipulators - Russo, Matteo; Dong, Xin (Mechanism and machine theory, 2020)
•A calibration procedure for a reconfigurable Gough-Stewart parallel manipulator is proposed.•Geometrical identification is achieved through distance measurements.•A general mathematical model for calibration is introduced.•The calibration procedure is validated on a reconfigurable robot. This paper introduces a calibration procedure for the identification of the geometrical parameters of a reconfigurable Gough-Stewart parallel manipulator. By using the proposed method, the geometry of a general Gough-Stewart platform can be evaluated through the measurement of the distance between couples of points on the base and mobile platform, repeated for a given set of different poses of the manipulator. The mathematical modelling of the problem is described and a numeric algorithm for an efficient solution to the problem is proposed. Furthermore, an application of the proposed method is discussed with a numerical example, and the behaviour of the calibration procedure is analysed as a function of the number of acquisitions and the number of poses.